THE ANALYSIS OF TABOO WORDS USED IN THE KISSING BOOTH’S SCRIPT MOVIE - Mathilda S Anung; Stanislaus Guna; Indra Susanto (Fakultas Hukum dan Sosial Humaniora Universitas Flores, 2026)
This research focuses on analyzing the types and functions of taboo words used in the Kissing Booth’s Script Movie. In this research, the researcher employed the Batistella classification (2005) and Jay (1996). The objective of the study is to find the types and functions of taboo words used in the Kissing Booth’s Script Movie. The researcher used descriptive qualitative in analyzing data. The data of this research were the character’s utterances in the Kissing Booth Script Movie. The instrument of this research is the researcher herself. The researcher collected the data by downloading the script, observing, documenting, analyzing the types and functions of taboo words, and classifying the types of taboo words. After getting the data, the researcher classified and analyzed the type of taboo words by each character. At the end of the analysis, the researcher concluded based on the types of taboo words and the functions of taboo words used. The result of this research showed 53 data containing all types of taboo words. Slang is the most frequently used with 18 utterances. Then, the second is profanity with 7 utterances. The third is obscenity with 6 utterances and vulgarity also cursing with 5 utterances. While, epithets, blasphemy, and insult have 3. Moreover, scatology has 2 utterances, and the less frequent is slur with 1 utterance. Thus, the researcher concluded that slang is the highest rank of taboo word employed by the characters of the Kissing Booth’s Script Movie. Meanwhile, the lowest type of taboo word employed by the characters of that film is a slur. This study highlights the importance of teaching students about taboo words and their functions through pragmatic competence. Teachers can use film excerpts to illustrate politeness strategies and encourage class discussions on language use in social contexts. Media literacy should also be integrated into language teaching, helping students analyze how films shape language, reflect social norms, and influence identity. This approach enhances critical thinking and prepares students for real-life communication